Orychophragmus violaceus as a winter cover crop is more conducive to agricultural sustainability than Vicia villosa in cotton-fallow systems. Issue 11 (19th September 2022) - Zhang, Zhenggui; Li, Xiaofei; Xiong, Shiwu; an, Jie; Han, Yingchun; Wang, Guoping; Feng, Lu; Lei, Yaping; Yang, Beifang; Xing, Fangfang; Xin, Minghua; Du, Wenli; et al.
ABSTRACT: The current cotton ( Gossypium hirsutum L.) fallow farming system causes soil degeneration and cotton yield reduction. Cover cropping is commonly associated with improved soil fertility and crop productivity, while the effect of cover crops on soil quality and cotton productivity remains unclear in the region. Using a monoculture cotton (cotton-fallow) as the control, a field experiment was conducted to verify the impacts of cotton with two cover crops, Orychophragmus violaceus (cotton/ O. violaceus ) and Vicia villosa (cotton/ V. villosa ), on soil chemical properties and cotton productivity. The results showed that cotton/ O. violaceus increased the soil organic matter (SOM), total nitrogen (TN), and available nitrogen (AN) by 5.77%, 2.03%, and 13.07% compared to cotton-fallow at a 0–100 cm soil depth, respectively. Cotton/ O. violaceus developed relatively greater cotton biomass accumulation and higher cotton yield than cotton/ V. villosa and cotton-fallow, an immediate cause of which was greater reproductive organ biomass accumulation and a larger number of bolls per unit area. Furthermore, SOM and TN had a significantly positive correlation with cotton biomass and yield. Cotton/ O. violaceus were more conducive than cotton/ V. villosa and cotton-fallow in the Yellow River basin of China and in other areas with similar requirements.